Theodicy: The Solution to the Problem of Evil, or Part of the Problem? - Trakakis, Nick (Sophia, 2008)
Theodicy, the enterprise of searching for greater goods that might plausibly justify God’s permission of evil, is often criticized on the grounds that the project has systematically failed to unearth any such goods. But theodicists also face a deeper challenge, one that places under question the very attempt to look for any morally sufficient reasons God might have for creating a world littered with evil. This ‘anti-theodical’ view argues that theists (and non-theists) ought to reject, primarily for moral reasons, the project of ‘justifying the ways of God to men’. Unfortunately, this view has not received the serious attention it deserves, particularly in analytic philosophy of religion. Taking my cues from such anti-theodicists as Kenneth Surin, D.Z. Phillips and Dostoyevsky’s Ivan Karamazov, I defend several reasons for holding that the way of thinking about God and evil enshrined in theodical discourse can only add to the world’s evils, not remove or illuminate them.